Pengaruh pH Agen Pereduksi Serin Terhadap Sintesis Nanopartikel Emas - Meiyanti Ratna Kumalasari; Zimon Pereiz; Chuchita Chuchita (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Synthesis of gold nanoparticles (AuNPs) using reducing agents and serine reservoirs has been carried out. The effect of pH has been studied to determine the optimum conditions for the formation of AuNPs. Characterization was performed using a UV/Vis spectrophotometer. The results showed that serine can act as a reducer and reservoir in the synthesis of AuNPs characterized by a change in color from colorless to burgundy. The highest absorbance intensity in the UV/Vis spectra indicates the optimum pH value in the formation of AuNPs. In this study, the maximum wavelength was in the 550 nm region and the highest absorbance intensity was obtained at pH 6.